2012
DOI: 10.1111/j.1754-9485.2012.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing local patients' knowledge and awareness of radiation dose and risks associated with medical imaging: A questionnaire study

Abstract: Patient radiation awareness is unsatisfactory. There is need to increase patient radiation awareness, and to provide them with the necessary information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
6
29
1
Order By: Relevance
“…However, reaching this goal may be challenging given that the physicians who order radiologic tests are typically not the same physicians who perform and interpret the tests; this situation creates a potential gap in patient communication that may result in a deficit in their understanding of these areas. For instance, past studies show that patients have incomplete knowledge regarding radiation exposure and risk from CT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, reaching this goal may be challenging given that the physicians who order radiologic tests are typically not the same physicians who perform and interpret the tests; this situation creates a potential gap in patient communication that may result in a deficit in their understanding of these areas. For instance, past studies show that patients have incomplete knowledge regarding radiation exposure and risk from CT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Medical radiologists themselves underestimate the radiation doses associated with a CT scan by 50-500 times [14] use ionizing radiation [15]. Such faulty knowledge is transferred directly onto patients when they discuss the reasons for having a medical imaging test and its related risks with medical specialists [16][17][18][19][20]. Nonetheless, no one knows the real level of awareness and perception of the risk arising from ionizing radiation in patients receiving diagnostic radiological procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that there is death of knowledge of radiation and related health hazards even among medical professionals who are referring as well as those intricately involved in performing radiological investigations. 6,8 Secondly, ignorance and underestimation of radiation hazards are noted in radiology professionals which is erstwhile not acceptable. 9 With knowledge of radiation hazards, principle of ALARA (as low as reasonably achievable) has also evolved in medical imaging.…”
Section: Discussionmentioning
confidence: 99%